The Indonesian Legal Paradigm: Between Pancasila Ideology and the Ethics of Artificial Intelligence (AI) Technology - Mohammad Saifuddin; Theresia Emilia B. Da Cunha (CV. Norma Global, 2025)
This article explores the intersection of Indonesia's fundamental philosophy, Pancasila, with the ethical and legal challenges posed by the rapid development of artificial intelligence (AI) technology. The development of AI is increasingly impacting various sectors of life, its integration raising critical concerns about regulations, human rights, social justice, and national values and identities. This study examines how Pancasila's values of divinity, humanity, national unity, democracy, and social justice can serve as normative guidelines in shaping an AI governance framework in Indonesia. By analysing the current legal infrastructure and identifying ethical gaps in AI applications, this paper proposes a contextual legal paradigm that aligns technological innovation with the moral and cultural principles enshrined in Pancasila. These findings suggest that a Pancasila-based legal approach can provide an ethical foundation in line with the goals of a nation grounded in national culture for the responsible development of AI in Indonesia.